Toward Gender Mainstreaming in Infrastructure Investment Projects: An Economic and Gender Dimension of Labour Framework, South Africa (Global Journal of Management and Business Research, 2023)
Effective and efficient conceptualisation and implementation of infrastructure investment is fundamental to every country's development. Many studies over decades have presented scientific evidence to this effect and it can be narrowly disputed. However, very few studies have been under-taken to point out the development inter-link of infrastructure investment and gender equality. What if further lacking, is the systems, tools and applicable frameworks which can provide scientifically based evident planning to ensure gender mainstreaming in infrastructure investment. Therefore, this paper proposes an Infrastructure Investment and Gender Dynamics of Labour Framework. The framework proposes factors to consider during the conceptualisation and implementation of infrastructure investment at macro level, meso level and micro level.
Keywords: gender equality; women empowerment; infrastructure investment; labour